Testing ontogenetic patterns of sexual size dimorphism against expectations of the expensive tissue hypothesis, an intraspecific example using oyster toadfish (Opsanus tau). Issue 7 (2nd March 2018) - Dornburg, Alex; Warren, Dan L.; Zapfe, Katerina L.; Morris, Richard; Iglesias, Teresa L.; Lamb, April; Hogue, Gabriela; Lukas, Laura; Wong, Richard
Abstract: Trade‐offs associated with sexual size dimorphism (SSD) are well documented across the Tree of Life. However, studies of SSD often do not consider potential investment trade‐offs between metabolically expensive structures under sexual selection and other morphological modules. Based on the expectations of the expensive tissue hypothesis, investment in one metabolically expensive structure should come at the direct cost of investment in another. Here, we examine allometric trends in the ontogeny of oyster toadfish ( Opsanus tau ) to test whether investment in structures known to have been influenced by strong sexual selection conform to these expectations. Despite recovering clear changes in the ontogeny of a sexually selected trait between males and females, we find no evidence for predicted ontogenetic trade‐offs with metabolically expensive organs. Our results are part of a growing body of work demonstrating that increased investment in one structure does not necessarily drive a wholesale loss of mass in one or more organs. Abstract : Organisms are faced with a finite energy budget with which to accumulate biomass in developing tissues, raising the question of how sexual selection imposes trade‐offs in organ investment. We test the expectations of the expensive tissue hypothesis (ETH) across the ontogeny of oyster toadfishes, a species in which males are under strong sexual selection for a metabolically expensive acoustic repertoire that involves maintaining the fastest twitching muscles of any vertebrates. However, despite finding clear evidence of sexual dimorphism, we failed to recover any evidence supporting the expectations of the ETH.